If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-9=3x(2-9)
We move all terms to the left:
2x-9-(3x(2-9))=0
We add all the numbers together, and all the variables
2x-(3x(-7))-9=0
We calculate terms in parentheses: -(3x(-7)), so:We get rid of parentheses
3x(-7)
We multiply parentheses
-21x
Back to the equation:
-(-21x)
2x+21x-9=0
We add all the numbers together, and all the variables
23x-9=0
We move all terms containing x to the left, all other terms to the right
23x=9
x=9/23
x=9/23
| 4x+3=-(x-13 | | 3+4f=-13 | | 51-3x=18 | | u+4/4=3 | | 5y-53=180 | | 19=m/2+16 | | 6(4x-12)=8x-8 | | 2+8x+59=79 | | 7x=18x+5 | | 9=d/4+6 | | 4(3x-1)=5(2x-7) | | 05/6x=3 | | -5x+2=-9x-7 | | 4(3x+7)=19x+4-7x+24 | | 4(2x-12)=2x-24 | | 4/5x=96 | | 2(3.375+-0.75y)+5Y=12 | | x+69=30 | | -24=8(2x+5) | | 6x+4=9x-29 | | 47+x+69=75 | | 48=6x+6 | | x+64=30 | | 3n/4-2=7 | | 10(3x-13)=-100 | | m–1.9=2.2 | | (2x+1)-(x+13)=3x^2-2x+2 | | x²-2x+1x=0 | | 6s+7=-47 | | x+129=124 | | 5h-38=12 | | 4+35=21x+8 |